PESANTREN SEBAGAI “KIBLAT” PENDIDIKAN DAN PENGETAHUAN INDONESIA - Jamal Ma’mur Asmani (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2016)
As the oldest educational institutions in Indonesia and typical, boarding has always been one the main reference in formulating national curriculum. For this reason this paper examines the contribution of educational boarding schools in Indonesia. Based on a qualitative approach through literature method of this paper found that boarding school is an educational institution that has educational value corresponding to the Indonesian people, so that in the course of its history, has always been a force in the boarding membntuk education system in Indonesia. Besides Indonesian pesantren is an educational institution that not only teach religion as such, but rather a general knowledge that equip pesantren alumni later when living in a community like interpeneurship or independent economy.